1986
DOI: 10.1007/bf00044880
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation pattern and environmental correlates in coastal forests of the Australian monsoon tropics

Abstract: A transect study o f coastal forest vegetation on a lateritic peninsula in the N o r t h e r n Territory revealed four distinct communities; eucalypt forest, mixed eucalypt f o r e s t -m o n s o o n thicket, pure m o n s o o n thicket and fringing coastal mangrove forest. The mangrove forest occurred in saline mud, the mixed and pure thicket on red earths and the eucalypt forest on both red and yellow earths. The eucalypt forest had less moisture in the surface soil t h a n the other communities on the gentle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…Dry season surfaee soil moisture eontent was not significantly different between the monsoon forest and savanna. This is in contrast to the findings of Bowman and Dunlop (1986) for a coastal monsoon forest-savanna boundary in the Northern Territory (NT). Russell-Smith (1986) measured xylem pressure potentials of some monsoon forest tree species which occur across savanna-forest boundaries in the NT.…”
Section: Environmental Controls Of Monsoon Forest-savanna Boundarycontrasting
confidence: 99%
See 2 more Smart Citations
“…Dry season surfaee soil moisture eontent was not significantly different between the monsoon forest and savanna. This is in contrast to the findings of Bowman and Dunlop (1986) for a coastal monsoon forest-savanna boundary in the Northern Territory (NT). Russell-Smith (1986) measured xylem pressure potentials of some monsoon forest tree species which occur across savanna-forest boundaries in the NT.…”
Section: Environmental Controls Of Monsoon Forest-savanna Boundarycontrasting
confidence: 99%
“…Bowman (1991) showed that, if late dry season fires transgress the boundary, most monsoon forest tree species have well developed vegetative recovery mechanisms. These facts account for the temporal stability of most monsoon forest boundaries (Bowman & Dunlop 1986). Differenees in fire regime may also account for the significantly higher concentrations of nutrients in monsoon forest soil than in savanna soils (Kellman 1984;Bowman & Mmchin 1987).…”
Section: Environmental Controls Of Monsoon Forest-savanna Boundarymentioning
confidence: 91%
See 1 more Smart Citation
“…Haynes, 1985;Bowman et al, 1988;Press et al, 1995), and are also started by lightning strikes. Fires have a strong in¯uence on vegetation composition and plant phenology (Bowman & Dunlop, 1986;Setter®eld & Williams, 1996).…”
Section: Study Area and Climatementioning
confidence: 99%
“…mangrove (e,g, Thom et al 1975;Wells 1981;Semeniuk 1985) and wetland (e.g. Williams 1979Williams , 1984, and with several detailed vegetation descriptions recently becoming available for particular areas (e,g, Specht et al 1917: Langkamp et al 1981Burgman & Thompson 1982;Beard et al 1984;Bowman & Wightman 1985;Rice & Westoby 1985;Taylor & Dunlop 1985;Bowman 1986;Bowman & Dunlop 1986). Much of the area of the wet/dry tropics consists of extensive plateaux whence arise the streams that flow into plain and wetland, and the dissected edges of which contain monsoon forests (Taylor & Dunlop 1985).…”
Section: Introductionmentioning
confidence: 99%